Total 18F-FDG PET/CT Metabolic Tumor Volume Is Associated With Postoperative Biochemical Response in Patients With Metastatic Pheochromocytomas and Paragangliomas - Patel, Dhaval (Ann Surg, 2016)
OBJECTIVE: The aim of this pilot study was to determine if metabolic tumor volume (MTV) and total lesion glycolysis (TLG) could serve as predictors of biochemical remission and pharmacotherapy-free interval in patients with metastatic pheochromocytomas (PCCs) and paragangliomas (PGLs). BACKGROUND: Patients with metastatic PCCs/PGLs have a high rate of biochemical recurrence, which can be associated with increased cardiovascular morbidity. Predictors of biochemical response are needed to guide and select patients who may benefit from therapy. METHODS: Whole body MTV and TLG was calculated from preoperative 18F-FDG PET/CT scans and analyzed as marker of biochemical response and pharmacotherapy-free interval. RESULTS: Seventeen patients underwent a total of 19 procedures, with a median follow-up time of 26.4 months. Whole body MTV of patients with biochemical recurrence (n = 13, mean 73.8 mL) was higher than those who had a biochemical response (n = 6, mean 14.7 mL, P = 0.05). Patients with low MTV (<37.2mL) had an improved durable partial biochemical response (P <0.05), and a statistical trend for complete biochemical remission (P = 0.07) and pharmacotherapy-free interval (P = 0.06). In 8 patients with metastatic disease outside the abdomen, 4 patients had less than 35% of their disease burden outside the abdomen and these patients had a more durable partial biochemical response compared to patients with greater than 35% of their disease burden outside the abdomen (P < 0.05). CONCLUSIONS: Whole body MTV and TLG represents novel and valuable predictors of biochemical response for patients with metastatic PCCs and PGLs. A larger prospective study should be performed to validate these findings.